Awareness and Feasibility of Women Chairing Cardiology Sessions in Scientific Meetings: A Nationwide Survey by the Japanese Circulation Society - Nakayama, Atsuko; Kamiya, Chizuko A.; Kanki, Sachiko; Ide, Tomomi; Bando, Yasuko K.; Uemura, Yukari; Tsukada, Yayoi Tetsuou (Frontiers in Cardiovascular Medicine, 2022)
Background: Diversity and inclusion remain a concern in the field of cardiology. Female cardiologists have less opportunity to chair sessions in scientific meetings than men. However, cardiologists’ awareness and perspectives on feasibility of chairing sessions is poorly understood. Methods and Results: A web-based survey on awareness regarding the commitment of chairing sessions was sent to 14,798 certificated cardiologists registered with the Japanese Circulation Society (JCS). A total of 3,412 valid responses were obtained, including 523 women and 2,889 men. Female cardiologists exhibited less interest in serving as chairpersons in Japanese and English sessions (71% women vs. 82% men, P<0.001, 30% women vs. 40% men, P<0.001). Influencing factors of chair acceptance in Japanese sessions for female cardiologists were being a cardiologist for over 10 years (odds ratio [OR] 1.84, 95% confidence interval [CI] 1.02–3.33), experience studying abroad (OR 3.35, 95%CI 1.93–5.81) and chairing sessions (OR 8.39, 95%CI 5.48–12.9), having a Doctor of Philosophy (OR 2.82, 95%CI 1.09–7.31), presence of four or more female cardiovascular specialists in the hospital (OR 1.70, 95%CI 1.10–2.61) and of role models (OR 2.86, 95%CI 1.93–4.24), and awareness of the JCS chairperson’s manual (OR 10.7, 95%CI 6.67–17.1). The receiver operating characteristic curve revealed that the number of female cardiovascular specialists in a hospital was a more sensitive predictor of chair acceptance among male than female cardiologists. Conclusions: Female cardiologists were less accept chairing sessions compared with male cardiologists and the presence of female cardiovascular specialists positively influenced chair acceptance.